An Empirical Investigation of Corporate Governance-Corruption Relationship: A Global Perspective (KASBIT Business Journal, 2021)
The study focuses on the relationship between the corruption perception index and mechanisms of corporate governance. We focus on a sample of 130 countries that are included in the data provided by the World Economic Forum and Transparency International from 2006 to 2017. Current research provides empirical evidence that the strength of investors’ protection and efficacy of corporate boards help control corruption and the country level. A panel regression model was used to examine the hypothetical relationships. The findings of the study suggest the negative relationship between the efficacy of corporate boards and the corruption perception index. Similarly, we found the negative impact of the strength of investor protection on the corruption perception index. Hence the results indicated that two of the above-mentioned corporate governance mechanisms i.e. the strength of investors' protection and efficacy of corporate boards help reduce corruption at the country level. The policymakers should continue to strengthen the legislation of corporate governance, and the management authorities should adopt corporate governance practices in the true spirit. Hence this paper contributes to existing research on corporate governance and corruption by taking the global perspective.
Keywords: Corruption perception index; the efficacy of corporate boards; the strength of investors’ protection